RAM analysis of dynamic positioning system: An approach taking into account uncertainties and criticality equipment ratings - Clavijo, Maria V; Schleder, Adriana M [UNESP]; Droguett, Enrique Lopez; Martins, Marcelo R (SAGE Publications, 2021)
Currently, a Dynamic Position (DP) System is commonly used for offshore operations. However, DP failures may generate environmental and economic losses; thus, this paper presents the Reliability, Availability and Maintainability (RAM) analysis for two different generations of DP system (DP2 and DP3) used in drilling operations. In addition to the RAM analysis, the approach proposed herein considers the uncertainties present in the equipment failure data and provides more information about criticality equipment ratings and probability density functions (pdf) of the repair times. The reliability analysis shows that, for 3 months of operation, the total failure probability of the DP2 system is 1.52% whereas this probability for the DP3 system is only 0.16%. The results reveal that the bus-bar is the most critical equipment of the DP2 system, whereas the wind sensor represents the priority equipment in the DP3 system. Using 90% confidence level, each DP configuration was evaluated for a 1-year operation, finding a reliability mean equal to 70.39% and 86.77% for the DP2 system and the DP3 system, respectively. The DP2 system asymptotic availability tends to present a constant value of 99.98% whereas for the DP3 system, it tends to be 99.99%. Finally, the maintainability analysis allows concluding that the mean time for system repair is expected to be 3.6 h. This paper presents a logical pathway for analysts, operators, and reliability engineers of the oil and gas industry.
Keywords: dynamic positioning system; fault tree analysis; Monte Carlo simulation; RAM Analysis; uncertainty propagation